(untitled) (Medical Forum Monthly, 2024)
Objective: To assess the Cutaneous manifestations of Diabetes Mellitus patients in tertiary care hospitals. Study Design: A cross-sectional study Place and Duration of Study: This study was conducted was outpatient departments of Dermatology, Medicine, Diabetic clinics of Jinnah Postgraduate Medical Centre, Civil Hospital, Baqai Endocrinology Centre from the 15th of May till the 30th of November 2011. Materials and Methods: A sample size of 145 diabetic patients with skin disorders selected through non-probability purposive sampling in outpatient departments of Dermatology, Medicine, Diabetic clinics of Jinnah Postgraduate Medical Centre, Civil Hospital, Baqai Endocrinology Centre. The Data Analysis was collected, analyzed on statistical packages of social sciences 17 Result: Out of 145 Diabetic patients, 63.4% were Females, 36.6% males. The mean age was 53.14 years. 77.9% had skin diseases, 55.9% experience skin lesions in the past. Female patients had higher frequency of skin disorders (92/145) than male diabetics (53/145). 69.7% had diabetes mellitus for more than 5 years; 11% who had diabetes for 5 years, 8.3% had it for 3 years, 8.3% for a year. Gangrene 46.20%, bacterial infections 30.3%, fungal infection 23.44%. Conclusion: The study concluded skin involvement occurs commonly in diabetics patients. Patients should be educated about blood glucose control, skin and foot care.